Cold-start icing characteristics of proton-exchange membrane fuel cells. (3rd May 2019) - Li, Linjun; Wang, Shixue; Yue, Like; Wang, Guozhuo
Abstract: Understanding the icing characteristics of proton-exchange membrane fuel cells (PEMFCs) is essential for optimizing their cold-start performance. This study examined the effects of start-up temperature, current density, and microporous layer (MPL) hydrophobicity on the cold-start performance and icing characteristics of PEMFCs. Further, the cold-start icing characteristics of PEMFCs were studied by testing the PEMFC output voltage, impedance, and temperature changes at different positions of the cathode gas diffusion layer. Observation of the MPL surface after cold-start failure allowed determination of the distribution of ice formation at the catalytic layer/MPL interface. At fuel cell temperatures below 0 °C, supercooled water in the cell was more likely to undergo concentrated instantaneous freezing at higher temperatures (−4 and −5 °C), whereas the cathode tended to freeze in sequence at lower temperatures (−8 °C). In addition, a more hydrophobic MPL resulted in two successive instantaneous icing phenomena in the fuel cell and improved the cold-start performance. Highlights: Cold-start icing in proton-exchange membrane fuel cells is investigated. Effects of temperature, current density, and MPL hydrophobicity are studied. Concentrated instantaneous icing occurs at relatively higher temperatures. Relatively lower temperatures cause sequential icing. A more hydrophobic microporous layer improves the cold-start performance.